KLITIK PRONOMINA DALAM BAHASA ANAKALANG - Editor Team (Jurnal Lazuardi, 2019)
Klitik is different from the affix. Although both are bound forms attached to the word that follows it or the word that follows it or added to the front of the word or added to the back of the word. Affixes in the Indonesian language, such as di-, meN-, BER, KE, TER-, PE-, and so on. As for the kl-ku, ku-, -mu, -nya. In the Anakalang language, it is found that there is only one affix 'affix', that is, pa-. This pa- prefix does not contain any meaning if this prefix stands alone without being attached to the basic word or basic form. Whereas klitik in BA is found in various forms, such as ku-, -gi, -me, -mi, -mu, -ne-, and -de on the Kripalu 'kupukul', kumanadangu 'kucantik', -gi 'ku' in the language Indonesia, as in umagi 'my house', palugi 'hit me', bahagi 'wet', bunkum 'our book or our book, palume' hit us or hit us', dowimi 'your money', dowimu 'your money' dowine 'money' , and dowide 'their money'